tính
11/4 - 6/7
8 - 7/45
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\dfrac{3}{7}\right)^2\cdot\left(-7\right)^4=\dfrac{9}{49}\cdot49^2=9\cdot49=441\)
\(\left(-11\right)^{12}\cdot\left(\dfrac{4}{11}\right)^4=11^{12}\cdot\dfrac{4^4}{11^4}=11^8\cdot4^4=54875873536\)
\(\left(-6\right)^8\cdot\left(\dfrac{5}{6}\right)^7=6^8\cdot\dfrac{5^7}{6^7}=6\cdot5^7=469750\)
4) \(\left(\dfrac{3}{7}\right)^2\cdot\left(-7\right)^4\)
\(=\left(\dfrac{3}{7}\right)^2\cdot\left[\left(-7\right)^2\right]^2\)
\(=\left(\dfrac{3}{7}\right)^2\cdot49^2\)
\(=\left(\dfrac{3}{7}\cdot49\right)^2\)
\(=\left(\dfrac{147}{7}\right)^2\)
\(=21^2\)
\(=441\)
5) \(\left(-11\right)^{12}\cdot\left(\dfrac{4}{11}\right)^6\)
\(=\left[\left(-11\right)^2\right]^6\cdot\left(\dfrac{4}{11}\right)^6\)
\(=121^6\cdot\left(\dfrac{4}{11}\right)^6\)
\(=\left(121\cdot\dfrac{4}{11}\right)^6\)
\(=44^6\)
6) \(6^8\cdot\left(\dfrac{5}{7}\right)^7\)
\(=6^8\cdot\dfrac{5^7}{6^7}\)
\(=\dfrac{6^8\cdot5^7}{6^7}\)
\(=6\cdot5^7\)
\(=469750\)
`4/7+4`
`=4/7+4/1`
`=4/7+28/7`
`=32/7`
__
`3+6/11`
`=33/11+6/11`
`=39/11`
__
`3-5/7`
`=3/1-5/7`
`=21/7-5/7`
`=16/7`
__
`21/9-2`
`=21/9-18/9`
`=3/9`
`=1/3`
__
`15/24+2`
`=15/24+48/24`
`=63/24`
`=21/16`
__
`63/45-20/25`
`=63/45-4/5`
`=63/45-36/45`
`=27/45`
`=9/15`
__
`3/4-2/8`
`=3/4-1/4`
`=2/4`
__
`6/7-5/8`
`=48/56-35/56`
`=13/56`
__
`37/45-5/9`
`=37/45-25/45`
`=12/45`
`=4/15`
__
`46/39-11/13`
`=46/39-33/39`
`=13/39`
`=1/2`
__
`5/12+3/4+1/3`
`=5/12+9/12+4/12`
`=14/12+4/12`
`=18/12`
`=3/2`
__
`1/2+3/7+11/14`
`=7/14+6/14+11/14`
`=13/14+11/14`
`=24/14`
`=12/7`
__
`7/10-(1/5+1/4)`
`=7/10-(4/20+5/20)`
`=7/10-9/20`
`=14/20-9/20`
`=5/20`
`=1/4`
__
`15/4-2/3-3/4`
`=(15/4-3/4)-2/3`
`=12/4-2/3`
`=3-2/3`
`=9/3-2/3`
`=7/3`
`a,`
`31/23-(7/32+8/23)`
`=31/23-7/32-8/23`
`=(31/23-8/23)-7/32`
`=1-7/32=25/32`
`b,`
`38/45-(8/45-17/51-3/11)`
`=38/45-8/45+17/51+3/11`
`= (38/45-8/45)+17/51+3/11`
`=2/3+17/51+3/11`
`=1+3/11=14/11`
`c,`
`(1/3+12/67+13/41)-(79/67-28/41)`
`= 1/3+12/67+13/41-79/67+28/41`
`= 1/3+(12/67-79/67)+(13/41+28/41)`
`= 1/3+(-1)+1=1/3+(-1+1)=1/3+0=1/3`
`d,`
`1/5+(-1/6)+1/7+(-1/8)+1/9+1/8+(-1/7)+1/6+(-1/5)`
`= (1/5+ -1/5)+(-1/6+1/6)+(1/7+ -1/7)+(-1/8 +1/8)+1/9`
`= 0+0+0+0+1/9=1/9 .`
a. -3/4 x 12/-5 x (-25/6)=-15/2
b. -2 x -38/21 x -7/4 x (-3/8)=-19/8
c. (11/12: 33/16) x 3/5=4/15
d. 7/23 x [(-8/6)- 45/18]=-7/6
Ta có:
a) ( 45 – 5 x 9 ) x 1 x 2 x 3 x 4 x 5 x 6 x 7
= (45 – 45) x 1 x 2 x 3 x 4 x 5 x 6 x 7
= 0 x 1 x 2 x 3 x 4 x 5 x 6 x 7
= 0
b) (1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10) x (72 – 8 x 8 – 8)
= (1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10) x (72 – 64 – 8)
= (1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10) x 0
= 0
c) (36 – 4 x 9) : (3 x 5 x 7 x 9 x 11)
= (36 – 36) : (3 x 5 x 7 x 9 x 11)
= 0 : (3 x 5 x 7 x 9 x 11)
= 0
d) (27 – 3 x 9) : 9 x 1 x 3 x 5 x 7
= (27 – 27) : 9 x 1 x 3 x 5 x 7
= 0 : 9 x 1 x 3 x 5 x 7
=0
a) ( 45 – 5 x 9 ) x 1 x 2 x 3 x 4 x 5 x 6 x 7
= 0 x 1 x 2 x 3 x 4 x 5 x 6 x 7
b) (1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10) x (72 – 8 x 8 – 8)
= (1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10) x 0
c) (36 – 4 x 9) : (3 x 5 x 7 x 9 x 11)
= 0 : (3 x 5 x 7 x 9 x 11)
d) (27 – 3 x 9) : 9 x 1 x 3 x 5 x 7
= 0 : 9 x 1 x 3 x 5 x 7 Nếu đúng thì k cho mình nhé bạn!
53/28
353/45
53/28
353/45